Early occurrence of new‐onset diabetes after transplantation is related to type of liver graft and warm ischaemic injury. (20th November 2014) - Hartog, Hermien; May, Christine J.H.; Corbett, Chris; Phillips, Angela; Tomlinson, Jeremy W.; Mergental, Hynek; Isaac, John; Bramhall, Simon; Mirza, Darius F.; Muiesan, Paolo; Perera, M. Thamara P.R.
Abstract Background & Aims We studied new‐onset diabetes after transplantation (NODAT) in liver transplantation with grafts donated after brain death (DBD) or circulatory death (DCD), focusing on the early post‐transplant period. Methods A total of 430 non‐diabetic primary liver transplant recipients [DCD, n = 90 (21%)] were followed up for 30 months (range 5–69). NODAT was defined as the composite endpoint of one of following: (i) Two non‐fasting plasma glucose levels > 11.1 mmol/L ≥ 30 days apart, (ii) oral hypoglycaemic drugs ≥ 30 days consecutively (iii) insulin therapy ≥ 30 days and (iv) HbA1c ≥ 48 mmol/L. Resolution of NODAT was defined as cessation of treatment or hyperglycaemia. Results Total of 81/430 (19%) patients developed NODAT. Incidence and resolution of NODAT over time showed significantly different patterns between DCD and DBD liver graft recipients; early occurrence, high peak incidence and early resolution were seen in DCD. In multivariate logistic regression including age, ethnicity, HCV, tacrolimus level and pulsed steroids, only DCD was independently associated with NODAT at day 15 post‐transplant (OR 6.5, 95% CI 2.3–18.4, P < 0.001), whereas age and pulsed steroids were significant factors between 30–90 days. Combined in multivariate Cox regression model for NODAT‐free survival, graft type, age and pulsed steroids were each independent predictor for decreased NODAT‐free survival in the first 90‐postoperative days. Conclusion Early peak of NODAT in DCD graft recipients is a novel finding, occurring independently from known risk factors. Donor warm ischaemia and impact on insulin sensitivity should be further studied and could perhaps be associated with graft function.